An Analysis of Spring-back and Spring-go on Variation of V-Dies Bending Angle Using Galvanized SGCC Steel Sheet - Khoirudin Khoirudin; Sukarman Sukarman; Siswanto Siswanto; Nana Rahdiana; Ade Suhara (Mechanical Engineering Department Universitas Buana Perjuangan Karawang, 2022)
This study discusses the phenomenon of spring-back and spring-go in the bending kinematic shaping process using V-bending dies and SGCC galvanized steel sheet (JIS G 3302) material. During the bending process, the zinc layer on the surface of the galvanized steel must not be damaged. The zinc coating on galvanized sheet steel will affect the material forming process (metal forming process). This study employed an experimental design with four input variables: die opening L (mm), punch angle (punch engel), punch speed (punch speed), and bending force (force bending). The input factors for the experiment are 35 mm opening, 40o punch angle, 30 mm/minute punch speed, and 7500 N bending force. In the die opening setting conditions, the maximum spring-back angle is 35 mm, the punch angle is 40 °, the punch speed is 30 mm/minute, and the bending force is 6500 N. The average minimum and maximum spring-back angles in this condition are 0.71o and 4.08o, respectively. The bending force is 7000 N, the punch angle is 50 °, the punch speed is 40 mm/minute, and the minimum spring-go angle is 30o. In die opening parameters, the maximum spring-go angle achieved is 35o, the punch angle is 60o, the punch speed is 50 mm/minute, and the bending force is 700 N. The average minimum and maximum spring-go angles are 1.90o and 6.23o, respectively.